Implementation of Special Education Fund in the Public Schools of Milagros - Pilapil, Mary Ann (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined teachers’ perceptions of the implementation, effectiveness, and challenges of the Special Education Fund (SEF) in public schools in Milagros, Masbate. Anchored on the Theory of Planned Behavior, Systems Theory, and Inclusive Education Theory, the study employed a quantitative descriptive-correlational research design. Data were collected from fifty (50) teachers through a researcher-made and validated questionnaire and analyzed using frequency counts, percentages, weighted means, rankings, and Pearson correlation. Findings revealed that the SEF was generally implemented in the areas of school infrastructure and facilities, instructional materials and equipment, co-curricular and extracurricular activities, and other school programs and services. The fund was perceived to be effective in supporting curriculum and instruction and highly effective in promoting school development and school operations. However, significant challenges were identified in the allocation and distribution of funds, monitoring and evaluation, and transparency and accountability. The results further showed a statistically significant positive relationship between the extent of SEF implementation and its perceived effectiveness, indicating that improved implementation contributes to better educational services and school outcomes. The study concludes that while the SEF effectively supports educational programs and school operations, improvements in resource allocation, monitoring systems, transparency, accountability, and stakeholder participation are necessary to enhance its implementation. The study aligns with Sustainable Development Goal (SDG) 4 on Quality Education, SDG 10 on Reduced Inequalities, and SDG 16 on Peace, Justice, and Strong Institutions by promoting inclusive education, equitable resource utilization, and responsible governance. Its sustainability contribution lies in strengthening educational, institutional, and community sustainability through improved management and utilization of educational resources.